CONNECTION OF MORPHOLOGIC FEATURES OF DURUM WHEAT (T.DURUM DESF.) WITH DROUGHT TOLERANCE - Kh. N. Rustamov; M. A. Abbasov (Зерновое хозяйство России, 2018)
The article considers the results of study of role of physical characteristics in ‘productivity during drought’ and drought tolerance of spring and winter wheat. It was found, that drought tolerance of durum wheat in different hydro thermal conditions and drought types was connected with different characteristics. It allowed us to conclude that a more reliable assessment was possible when using several methods and technologies simultaneously, based on various physiological criteria. It was revealed that the more tolerant to drought varieties showed larger figures of water-holding capacity. Among the traits which allow recognizing drought tolerance we can note high values of water loss while wilting and low values of a net productivity of photosynthesis. We found essential to use a math method of statusmetria to make large amount of productive and physiological data more informative and compact. The use of statusmetria gave us an opportunity to find differences in the samples’ reaction to drought depending on the time and duration. We found and gave quantitative assessment of those morpho physiologic parameters, which show the most productivity and stability under definite hydro thermal conditions. To create drought tolerant primary material we suggest combining the study of breeding material by screening, express methods with further detailed study of yield stability and morpho physiologic features of drought tolerance of the samples.